Evaluation of Three Commercial Serological Tests with Different Methodologies To Assess Helicobacter pylori Infection - van der Ende, A. (American Society for Microbiology, 1999)
The sera of 142 Helicobacter pylori-positive and 32 H. pylori-negative patients were assessed by a desktop test (QuickVue), an enzyme-linked immunosorbent assay (ELISA) (HM-CAP), and a solid-phase, two-step chemiluminescent enzyme immunoassay (Immulite). These tests yielded sensitivities of 97, 97, and 91% and specificities of 97, 94, and 100%, respectively. In conclusion, the desktop test and the ELISA are more sensitive than the chemiluminescent enzyme immunoassay (P < 0.05). The chemiluminescent enzyme immunoassay has the advantage that it is fully automated.